Supplementation of cereal straws with lucerne and sugar beet pulp in diets for ruminants - Gonzalez Vargas, Diego (The University of Edinburgh, 1987)
The aim of this work was to study the effects of supplementing untreated (US) and ammonia-treated (TS) barley straw with lucerne (L) and/or unmolassed sugar beet pulp (BP) on the digestibility and intake of the dietary components in ruminants. Coarsely shredded straw was fed ad libitum and pelleted supplements at restricted levels.

Rumen-fistulated steers and wethers were offered a diet containing (g/kg diet, DM basis): 760 US and 240 L. The in sacco degradation of US and L, estimated with the dacron bag technique, was similar for both species at most incubation times (5, 8, 11, 14, 24, 48 and 72 h). The differences for pH, ammonia-nitrogen (NH₃-N) and volatile fatty acids (VFA) in the rumen were small and inconsistent among times post-feeding. The daily straw organic matter intake (OMI, per kg LW⁰.⁷⁵ or LW⁰.⁹) was higher in steers than in wethers.

In two experiments, mature rumen-fistulated wethers were offered either US or TS supplemented with L at levels of (g/kg diet, DM basis): 0, 160, 320 and 480. These diets were also fed to 35-kg wethers in two digestibility and intake trials. Increasing the level of lucerne had little or no effects on the in sacco degradation of straw and lucerne nor on most parameters of rumen fermentation. The in vivo digestibility and metabolizable energy (ME) of the diets and the N retained by the sheep increased linearly as the level of lucerne increased. The organic matter digestibility (OMD) and ME for US and TS fed alone were 0.40 and 0.60 and 5.1 and 8.5 MJ per kg DM, respectively. There was little or no replacement of the straws by lucerne.

Comminution and passage of chromium-mordanted straws were studied with mature rumen-fistulated wethers offered four diets: US and TS alone or supplemented with L at 480 g per kg diet, DM basis. The rates of comminution of large straw particles (retained on sieves with aperture size > 1.18 mm) in the rumen were similar among treatments (0.055 per h). The rate of escape of small straw particles (passing through a 1.18-mm sieve) from the rumen was faster for the supplemented TS (0.033 per h) than for the other diets (0.021 per h).

In two experiments, mature rum en-fistulated wethers were offered either US and pellets at 320 g per kg diet, DM basis or TS and pellets at 480 g per kg diet, DM basis. The pellets contained L:BP in the following relative proportions: 3:0 (US-OBP and TS-0BP); 2:1 (US-33BP and TS-33BP); 1:2 (US-67BP and TS-67BP) and 0:3 (US-100BP and TS-100BP). The diets were also fed to 35-kg wethers in two digestibility and intake trials. Although the differences were mostly non-significant, rumen pH and NH₃-N tended to decrease while total rumen VFA tended to increase as the level of BP increased. The in sacco degradation of straw tended to be higher for diet US-100BP than for diet US-OBP. It tended to increase between diets TS-0BP and TS-67BP and then to decrease for diet TS-100BP. There were indications of positive associative effects of L and BP (1:2 ratio) on the intake and/or digestibility of the total diet. The US-OMI increased linearly whereas the TS-OMI remained constant as the level of BP increased.

It was concluded that lucerne and sugar beet pulp were effective supplements for barley straws as they generally maintained or increased the digestibility and/or intake of the straws and also increased significantly the intake of digestible nutrients.